Launching of the fifth volume of the scientific journal “Ambiente & Água” - Getulio Teixeira Batista (Revista Ambiente & Água, 2010)
This first issue of volume five contains 16 inedited peer reviewed papers from 59 authors that originated from three continents, 25 universities from which 12 are federal universities, 7 are state universities, three are from a municipal university from Brazil and three from abroad. Other four authors are from research institutions. We proudly state that this twelfth edition has been published on time as it happened with all previous issues. Most articles of this issue concentrate on environmental characterization of different ecosystems and on water quality assessment of several river basins. Then, there two articles on water reuse and two on environmental chemistry. The others relate to sediments, water treatment and hydropower impacts investigations.